Data Security Applications for School by Using Android - Sipahutar, Lahmudin; Handayani, Nursyah (Institut Teknologi Bisnis AAS Indonesia, 2025)
School is an agency that operates in the field of education. The school uses Microsoft Office applications to support the school system regarding the grades of students' lessons. The teacher will input student grades in the form of a report card or report on student grades in the form of numbers, while students will see the grades that have been input by the teacher in the report card or report on student grades. However, the value data in the student's report card or report has not undergone an encryption process, or in other words, it is still in plaintext form. This will certainly make it easier for unauthorized parties to read and manipulate student grade data if the grade data is still in plaintext. Therefore, some literature states that the way to solve this problem is by applying cryptography. To maintain data security and avoid data leaks, various methods can be used, one of which is by using cryptography. Cryptography is the process of hiding or coding information so that only the person a message was intended for can read it. The art of cryptography has been used to code messages for thousands of years and continues to be used in bank cards, computer passwords, and ecommerce.